Farmer preferences in using local Chinese mustard green seeds (Brassica chinensis var. parachinensis) in Kebonagung Village, Kaliwates District, Jember District - Syah, Wildan Iqyan; Novikarumsari, Nurul Dwi (Agriekonomika, 2025)
Kebonagung village is one of the areas in Jember Regency that has potential as a producer of Chinese mustard green. The cultivation process for caisim mustard in Kelurahan Kebonagung still uses local seeds as the production input. Therefore, this research aims to analyze farmers' preferences in using local Chinese mustard green seeds. The analysis method used is factor analysis with the assistance of IBM SPSS Statistics 24 software. The research results indicate that farmers' preferences in using local Chinese mustard green seeds are formed by 6 attributes: fertilizer use, seed germination capability, seed quality, soil type, pest and disease resistance, and seed stock. Based on the analysis results, the seed quality attribute is excluded from the model, thus farmers' preferences in using local seeds are based on 5 attributes: fertilizer use, seed germination capability, soil type, pest and disease resistance, and seed stock. Furthermore, based on the rotation process, they are grouped into 2 factors: external factors (fertilizer use and soil type) and internal factors (seed germination capability, pest and disease resistance, and seed stock).